Catalytic Dehydrogenation of Amine‐Boranes using Geminal Phosphino‐Boranes. Issue 13 (3rd February 2020) - Boom, Devin H. A.; de Boed, Ewoud J. J.; Nicolas, Emmanuel; Nieger, Martin; Ehlers, Andreas W.; Jupp, Andrew R.; Slootweg, J. Chris
Abstract : The reaction of the intramolecular frustrated Lewis pair (FLP) t Bu2 PCH2 BPh2 with the amine‐boranes NH3 · BH3 and Me2 NH· BH3 leads to the formation of the corresponding FLP‐H2 adducts as well as novel five‐membered heterocycles that result from capturing the in situ formed amino‐borane by a second equivalent of FLP. The sterically more demanding t Bu2 PCH2 BMes2 does not form such a five‐membered heterocycle when reacted with Me2 NH· BH3 and its H2 adduct liberates dihydrogen at elevated temperatures, promoting the metal‐free catalytic dehydrogenation of amine‐boranes. Abstract :